Relics from the original Walkeshwar Temple - Ghosh, Ayan (2023)
This heavily eroded panel is placed on the steps leading down to Banganga Tank. These stone panels are believed to have been part of from the old Walkeshwar Temple built by the Shilahara rulers. After the temple was demolished by the Portuguese, many of the broken pieces were salvaged and now lay scattered around the tank. The British took some of the better-preserved carvings to England and are now displayed at the India House Museum at South Kensington.